Cell membrane-bound toll-like receptor-1/2/4/6 monomers and -2 heterodimer inhibit enterovirus 71 replication by activating the antiviral innate response - Sun, Ping-Ping; Li, Dan; Su, Meng; Ren, Qing; Guo, Wen-Ping; Wang, Jiang-Li; Du, Luan-Ying; Xie, Guang-Cheng (Frontiers in Immunology, 2023)
Host immune activation is critical for enterovirus 71 (EV71) clearance and immunopathogenesis. However, the mechanism of innate immune activation, especially of cell membrane-bound toll-like receptors (TLRs), against EV71 remains unknown. We previously demonstrated that TLR2 and its heterodimers inhibit EV71 replication. In this study, we systematically investigated the effects of TLR1/2/4/6 monomers and TLR2 heterodimers (TLR2/TLR1, TLR2/TLR6, and TLR2/TLR4) on EV71 replication and innate immune activation. We found that the overexpression of human- or mouse-derived TLR1/2/4/6 monomers and TLR2 heterodimers significantly inhibited EV71 replication and induced the production of interleukin (IL)-8 via activation of the phosphoinositide 3-kinase/protein kinase B (PI3K/AKT) and mitogen-activated protein kinase (MAPK) pathways. Furthermore, human–mouse chimeric TLR2 heterodimers inhibited EV71 replication and activated the innate immunity. Dominant-negative TIR-less (DN)-TLR1/2/4/6 did not exert any inhibitory effects, whereas DN-TLR2 heterodimers inhibited EV71 replication. Prokaryotic expression of purified recombinant EV71 capsid proteins (VP1, VP2, VP3, and VP4) or overexpression of EV71 capsid proteins induced the production of IL-6 and IL-8 via activation of the PI3K/AKT and MAPK pathways. Notably, two types of EV71 capsid proteins served as pathogen-associated molecular patterns for TLR monomers (TLR2 and TLR4) and TLR2 heterodimers (TLR2/TLR1, TLR2/TLR6, and TLR2/TLR4) and activated innate immunity. Collectively, our results revealed that membrane TLRs inhibited EV71 replication via activation of the antiviral innate response, providing insights into the EV71 innate immune activation mechanism.